HURDLE RACE IN EARLY EDUCATION – 10 WEEKS OF ARTS AND PHYSICAL ACTIVITIES - Iskra, Janusz; Walaszczyk, Anna; Przednowek, Karolina (PEOPLE: International Journal of Social Sciences, 2017)
Research objectives. Hurdling (in sport = hurdle run, in schools = run through obstacles) is an interesting and really natural activity. Hurdle run is a test of speed (hurdle run is a sprint run), strength (hurdle clearance = hurdle “jumps”), coordination (rhythm, balance), flexibility and a lot of mental (courage). Methodology. In this experiment participated 33 girls from Polish primary school aged 12 years. In order to choose the adequate equipment for teaching hurdle run we settled on banana cardboard boxes (50x40x24cm). Within the period of 10 weeks we organized physical education lessons (2 times a week, 25 minutes were devoted to “hurdle lesson”). Before and after the 10 weeks hurdle preparation period we assessed: motor preparation (acceleration/30 m run, speed/60 m run, speed endurance/180 m run, explosive strength (standing triple jump an medicine ball throw) and special-hurdle abilities (time of 60 m hurdle run, number of steps between hurdles and “technique indicator”). Findings and research outcomes. Ten weeks of “hurdle training” increase time of speed run (60 m - p≤ 0, 01) and hurdle run (p≤0, 05). There were statistical significant differences between the number of stride “pattern” (p≤0, 01), too. Ten weeks of hurdle “training” didn’t change the level of rest of general and special tests. The analysis of correlation shows that hurdle race is a speed and strength athletic event. Practical application. Hurdle race (on initiation/school level) could be an interesting and creative form of physical education. The obstacle sprint run could be a reliable test of physical abilities.